(untitled) (Revista Electrónica REDINE, 2019)
The present investigation focuses on analyzing the conceptual framework on the technical criteria for the design of curricular materials at the University Pedagogical Experimental Libertador, Institute Pedagogical of Barquisimeto "Luis Beltrán Prieto Figueroa. The study was placed in the positivist paradigm with a quantitative approach, under the modality of documentary research. The research phases were organized in (a) selection and delimitation of the topic to be investigated, (b) collection of the information, (c) analysis of the selected material as a source of information. The techniques used were the critical analysis, the graphic technique, to later pass to the process of elaboration of intellectual production. It is established that the curricular material is consolidated as a support tool in the construction of knowledge, consolidating in the students their knowledge, values ​​and cognitive abilities to operate with them as a complex system of theoretical-practical knowledge in solving problems and needs personal and group.